2021
DOI: 10.1177/2192568220984129
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Kyphoplasty Versus Percutaneous Vertebroplasty for Neurologically Intact Osteoporotic Kümmell’s Disease: A Systematic Review and Meta-Analysis

Abstract: Study Design: Systematic review and meta-analysis. Objective: Percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) are minimally invasive techniques widely used for the treatment of neurologically intact osteoporotic Kümmell’s disease (KD), but which treatment is preferable remains controversial. Therefore, this study aimed to shed light on this issue. Methods: Six databases were searched for all relevant studies based on the PRISMA guidelines. Two investigators independently conducted a qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(106 reference statements)
2
11
0
Order By: Relevance
“…A long-standing perception of IVC as a sign of instability may be a consequence of the fibrocartilaginous membrane surrounding the IVC, which prevents cement diffusion and observes an unsatisfactory bonding between the cement and the surrounding cancellous bone ( 34 ). Thus, it is logically a sign of surgical complications including recollapse and residual low back pain ( 35 , 36 ). Yu et al systematically reviewed substantial studies and summarily reported a significant therapeutic efficacy in OVCF patients with percutaneous vertebral augmentation, but IVC was responsible for more frequent recollapse and unfavorable radiological parameters compared to controls ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing perception of IVC as a sign of instability may be a consequence of the fibrocartilaginous membrane surrounding the IVC, which prevents cement diffusion and observes an unsatisfactory bonding between the cement and the surrounding cancellous bone ( 34 ). Thus, it is logically a sign of surgical complications including recollapse and residual low back pain ( 35 , 36 ). Yu et al systematically reviewed substantial studies and summarily reported a significant therapeutic efficacy in OVCF patients with percutaneous vertebral augmentation, but IVC was responsible for more frequent recollapse and unfavorable radiological parameters compared to controls ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…PVP and PKP are considered the ideal methods to treat OVCFs with IVC [31]. However, some studies still report that the presence of preoperative IVC during long-term follow-up will more or less affect the clinical outcome after PVP, such as vertebral body recollapse, severe over residual back pain, or even compression fractures of adjacent vertebrae [13,32]. e presence of IVC sign in OVCFs has been reported to be a major risk factor for postoperative recollapse of the injured vertebra, progressive kyphosis, and chronic back pain [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…PVP or PKP could be used to strengthen the injured vertebrae. Both of them provided similar ain relief, but PKP is superior to PVP in restoring vertebral height and reducing cement leakage [10].…”
Section: Discussionmentioning
confidence: 96%